간호대학신입생의 정서인식, 정서표현, 정서표현양면성이 대학생활적응에 미치는 영향 - 김근면(Geun Myun Kim); 차선경(Sunkyung Cha) (한국콘텐츠학회 논문지, 13(1), 2013)
This study was done to investigate emotional awareness, emotional expressiveness, ambivalence over emotional expressiveness, and college student adjustment, to analyze the factor affecting college student adjustment. The subjects were 159 freshman nursing students. Data were collected through structured questionnaires from May 20 to June 10, 2012. Data analysis was done using descriptive statistics, independent t-test, ANOVA, Pearson correlation coefficient, and multiple regression with SPSS WIN v 18.0. Positive correlation were found between college student adjustment and mood monitoring as well as mood labeling. On the other hand, ambivalence over positive emotional expressiveness and ambivalence over negative emotional expressiveness were significantly negative correlation with college student adjustment. In addition, mood monitoring, ambivalence over positive emotional expressiveness, mood labeling, and ambivalence over negative emotional expressiveness accounted for 31.8% of variance in college student adjustment. The results of this study suggest that programs for promoting emotional awareness and reducing ambivalence over emotional expressiveness are important for college adjustment in freshman nursing students. 본 연구는 간호대학신입생의 정서인식, 정서표현, 정서표현양면성과 대학생활적응을 확인하고 대학생활 적응에 영향을 미치는 요인을 파악하고자 수행되었다. 연구대상은 4년제 대학 2곳에 재학 중인 간호학과 신입생 159명이었고, 구조화된 설문지를 이용하여 2012년 5월 20일부터 6월10일까지 자료조사를 실시하였다. 대학생활적응은 정서주의와 정서명명과는 유의미한 양의 상관관계를 보였고, 긍정표현에 대한 양면성과 부정표현에 대한 양면성과는 유의미한 음의 상관관계를 나타냈다. 대학생활적응에 가장 큰 영향을 미치는 요인은 정서주의였으며, 정서주의, 긍정표현에 대한 양면성, 부정표현에 대한 양면성, 정서명명은 대학생활 적응에 대해 31.8%의 설명력을 나타내었다. 간호대학신입생의 대학생활적응 향상을 위해서 정서인식 및 정서표현양면성을 돕는 교육 프로그램의 개발이 필요하다.